Mali : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report assesses the state of public investment management in Mali. The institutional strength of the public investment management framework is good compared with peer countries. The assessment of the 15 institutions (or components) of the framework pictures generally good scores, at or above average levels for low-income countries in almost all components. There are four exceptions: (1) the institutional framework for public private partnerships is incomplete; (2) there is scope for improvement in accounting and valuation of assets; (3) availability of financing for investments suffers from poor commitment management and cash flow projections; and (4) project assessment is not systematic or comprehensive. These deviations from good practices are being corrected with the implementation of the new legal framework.